ANALISIS KEMAMPUAN SISWA MENYELESAIKAN SOAL BERBENTUK GRAFIK PADA MATERI USAHA GAS DI MADRASAH ALIYAH - Albab, Uwly; Djudin, Tomo; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research aimed to find out student’s ability in solving the graph of work done by gas. The method of this research was a descriptive survey. 134 students of 12th grade in MAN 2 Pontianak were chosen as the sample of this research by using saturation sampling technique. Open-ended multiple choice items test (4 questions) and essay test (4 questions) were used to represent three indicators of student’s ability, and unstructured interview was also used to find out the factors that caused students’ error. Based on the analysis data, was found that the average of the ability of all sample in solving the graph of work done by gas was 39,03 (categorized as low). Based on the result of Mann Whitney U-Test, was found there is a significant difference (zcount: 2,73 >ztable: 0,997), that students with better mathematical ability (high group) have better ability in solving question on the graph of work done by gas than students with lower mathematical ability (low group). The students who were unable to solve the graph of work done by gas, were caused by low conceptual ability, low spatial ability, low remembering ability, low mathematical ability, and students’ lack of interest in the subject. These findings are expected to be the references to improve the students’ ability in solving the graph of work done by gas. Keywords:  Descriptive, Graph, Work Done by Gas, Student’s Ability.